IMPLEMENTASI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 45 JAKARTA - Rustian, Ihsan Harits; Ulfah, Maria (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This article aims to explain the implementation of the Contextual Teaching and Learning (CTL) approach in PAI learning at SMAN 45 January. This article uses a case study approach, and is a type of qualitative research. Data collection methods use interviews, observation and documentation. Data analysis uses descriptive analytical methods. The research results show that 1) The implementation of CTL is quite good, starting from planning the preparation of learning plans, selecting methods that are appropriate to learning, using diverse material sources, using facilities and infrastructure to support learning, as well as authentic assessment; 2) The results of the implementation of CTL also show quite a good impact on students, starting from learning methods that no longer focus on the teacher, students who do not feel bored and fed up when learning takes place, students who can think critically, and students who can implement the material taught by the teacher.